2019
DOI: 10.1186/s12978-019-0763-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of use of mobile phones for sexually transmitted infections (STIs) education and prevention among adolescents and young adult population in Ghana: implications of public health policy and interventions design

Abstract: Background Sexually Transmitted Infections (STIs) are a major public health challenge globally especially among adolescents and young adults in lower-middle-income countries (LMICs) in Africa including Ghana. In light of this, mobile phone innovations are advocated to enhance public health education and prevention of STIs in developing health systems. Objective This study assessed mobile phone usage among adolescents and young adult populations pursuing tertiary educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 25 publications
3
27
0
5
Order By: Relevance
“…For mobile owners compared to non-owners, the odds of having a comprehensive knowledge of HIV instead of low to moderate knowledge of HIV was higher by more than 27%. This finding is similar to the study done on adolescents from the United States and Botswana, where [36,37,39]. This puts mobile phones at the heart of other strategies used to disseminate HIV/AIDS-related educations and awareness creations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For mobile owners compared to non-owners, the odds of having a comprehensive knowledge of HIV instead of low to moderate knowledge of HIV was higher by more than 27%. This finding is similar to the study done on adolescents from the United States and Botswana, where [36,37,39]. This puts mobile phones at the heart of other strategies used to disseminate HIV/AIDS-related educations and awareness creations.…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to differences in access to mass media between urban and rural youths which play a very vital role in disseminating HIV-related educations and awareness creations. This study and other studies [18,[29][30][31][32][33][34][35][36][37][38][39] depicted that exposure to mass media is associated with acquiring comprehensive HIVknowledge.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Penelitian cross sectional yang dilakukan pada 250 remaja di Ghana menunjukkan bahwa aplikasi android merupakan fungsi android yang kedua yang paling sering digunakan setelah panggilan telpon, dimana 162 responden (64,8%) mengatakan mereka sering menggunakan fungsi ponsel ini. Rata-rata penggunaan aplikasi ini oleh peserta selama 48 menit perminggu (8) . Hampir semua responden di pulau Rohde menyatakan akan menggunakan aplikasi untuk belajar tentang kesehatan reproduksi (28) .…”
Section: Informasi Lengkap Tentang Kesehatan Reproduksi Dan Seksualunclassified
“…Mobile phone usage has changed in the last decade, with average data usage climbing from 0.2GB per month in 2012 to 1.9GB per month in 2017 and continues to increase, while SMS usage has decreased with outgoing SMS messages reducing from 162 in 2012 to 82 in 2017 [12]. In 2013, several studies indicated younger audiences favoured SMS communication [95,96] but more recently younger audiences have shown to prefer mobile applications for education over SMS messages [97]. Apps have the ability to reach a wider audience, with an app for adolescent sexual education in New York being downloaded over 22 ,000 times [98].…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%